Eph receptor tyrosine kinases in cancer stem cells. Issue 1 (February 2015) - Chen, Jin; Song, Wenqiang; Amato, Katherine
Abstract: Eph receptor tyrosine kinases (RTKs) and their ligands, ephrins, play critical roles in development, tissue homeostasis, and cancer. Because Eph receptors are expressed in most adult stem cell niches and in many types of cancers, it has been long suspected that this family of RTKs may also regulate the function of cancer stem-like cells (CSCs). This review will focus on recent studies to elucidate the contribution of Eph/ephrin molecules in CSC self-renewal and tumorigenicity, as well as describe efforts to target these molecules in cancer. Because CSCs are often resistant to therapeutic intervention and have been shown to depend on Eph RTKs for self-renewal, targeting Eph receptors may hold promise for the treatment of drug-resistant cancers.